Balloon mitral valvuloplasty: a re-emerging technique enhanced with real-time, three-dimensional transoesophageal cardiac ultrasound/echocardiography (3D-TOE). Issue 2 (7th February 2023) - Islam, Samsul; Khan, Jawad; Khan, Yusuf
Abstract : We describe the case of a woman in her 60s with mitral stenosis, rate-controlled atrial fibrillation and a history of childhood rheumatic fever. She successfully underwent elective percutaneous transvenous mitral commissurotomy (PTMC), also described as balloon mitral valvuloplasty, for severe, symptomatic mitral stenosis. This was completed via right femoral vein access, trans-septal puncture and commissural separation guided by real-time three-dimensional (3D) transoesophageal echocardiography under general anaesthesia. Balloon mitral valvuloplasty is being completed more frequently in the UK due to the population having a higher incidence of mitral valve disease as a result of migration and as a palliative measure in those considered too high risk for mitral valve replacement cardiothoracic surgery. Rheumatic mitral stenosis is known to be a disease prevalent in countries of low and middle income and with increased migration to the UK, resulting in an increased prevalence of rheumatic mitral valve disease in the UK. It is estimated that within the UK, one in seven persons are migrants, and as such, we believe it is important to pay attention to diseases which affect the evolving population of the UK. Technological advancements, including availability and use of 3D transoesophageal cardiac ultrasound/echocardiography, have made PTMC much safer and more effective than previously. Additionally, the multidisciplinary team approach to PTMC is very important to its success. The procedure was completed successfully, with no complications.